Integration of ICT in education : an Islamic perspective. - , Abdul Hafeez; Muhammad, Muhd. Rosydi; Shah, Asadullah (IIUM Press, 2011)
Rapid increase in the development of Information & Communication Technologies (ICTs) and the desire of obtaining education has left the society with no choice of education through ICTs. Education facilitated by the new ICT is transforming learning and instruction forms in ways "that extend beyond the efficient delivery or entertainment value of traditional approaches". Education in Islam is considered as an instrument by which people can be trained in the Islamic way of life. It's challenging to achieve the objective of Islamic education through ICTs. This paper discuses the integration of ICTs in education, highlight the objective of Islamic education and then finally suggests an innovative approach to obtain desired objectives.